Análise da eficiência e confiabilidade em 56 estações de tratamento de esgotos localizadas na região metropolitana de Fortaleza - Monteiro, Carlo Rannyêr Lopes (2009)
Many Wastewater Treatment Plants (WWTPs) have serious design and / or operational problems that decrease efficiency levels and pollute the environment. Thus, it is important to have efficient and reliable WWTPs to meet the discharge standards. The purpose of this study was to analyze the efficiency and reliability of 56 wastewater treatment plants located in the Metropolitan Region of Fortaleza (MRF). About 13,100 data were evaluated, which were obtained from the Company of Water and Wastewater of Ceará (CAGECE). The data were from January 2005 to April 2009, divided in nine treatment technologies: septic tank (ST), septic tank followed by anaerobic filter (ST + ANF), septic tank followed by anaerobic filter and chlorination (ST + ANF + Cl), facultative pond (FP), facultative pond followed by a maturation pond (FP + MP), anaerobic pond followed by facultative pond and maturation pond (ANP + FP + MP), facultative aerated pond followed by facultative pond and maturation pond (FAP + FP + MP), UASB reactor (UASB) and finally UASB reactor followed by chlorination (UASB + Cl). To calculate the reliability of WWTPs and expected attendance percentage to accomplish effluent standards, a log-normal distribution was used. The average concentrations that the effluent from WWTP must have to meet the discharge standard were calculated for a given reliability level (95%), taking into account the coefficient of reliability (COR). The affluent values of pH, COD, TSS and TTC were compared to those typically found for this type of wastewater. The initial data analysis indicated problems in the monitoring frequency, inconsistencies and outliers, which were removed. The resulting data were used afterwards. The average efficiency values obtained in some technologies are lower than those of comparative literature, indicating operational problems. The highest efficiency values for COD, TSS and TTC were achieved with the technologies of ANP + FP + MP (91,4%), ANP + FP + MP (81.0%) and FAP + FP + MP (99.999%); the lowest efficiencies were obtained with ST + ANF (47.3%), ST (31.6%) and FP (95.36%), respectively. Regarding the coefficient of reliability calculation, the highest values for COD removal were obtained with the technologies of FAP + FP + MP (0.57) and UASB (0.57) and the lowest efficiencies were found with DD + ANF + Cl (0.40). For TSS, the best technologies were FAP + FP + MP (0.43) and FP (0.41) while the lowest CORs were obtained with ANP + FP + MP (0.26). The highest percentage values for accomplishing COD discharge standards were achieved with stabilization ponds, all above 98%, specially the technology FAP + FP + MP (99.9%). For TSS the highest percentages were also achieved with stabilization ponds, highlighting the technology of ANP + FP + MP (91%). The technologies of FAP + FP + MP and ANP + FP + MP provided the best efficiency values for COD, TSS and TTC, as well as the highest values of COR and percentages to accomplish discharge standards.